2020
DOI: 10.12982/cmujns.2020.0064
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C, Chlorophyll Content and Total Phenolic Compounds in Artemisia lactiflora as Affected by Different Organic Fertilizers

Abstract: The objectives of this current study were to determine the varying contents of vitamin C, chlorophyll, total phenolic compounds in White mugwort (Artemisia lactiflora) which were tested under different types of organic fertilizer. Completely randomized design with four treatments (applications of no fertilizer, cow, chicken and bat manures) was assigned for the field experiments at Department of Medicinal Plant Science, Faculty of Agricultural Production, Maejo University in Chiang Mai, Thailand. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Likewise, Ahmed et al [26] reported that increasing the dose of N fertilizer increased the ascorbic acid of Cactus Pears Fruits. Meanwhile, the application of cow manure and 100 kg ha 1 NPK fertilizer was able to reduce sweetness level of sweet corn, which is not in accordance with Taeotankencan et al [31], mentioning that the Artemisea lactiflora produced high vitamin C when treated with cow manure. The combination of chicken manure and NPK fertilizer at doses of 300-400 kg ha -1 was able to increase the pro-vitamin A content of sweet corn.…”
Section: Discussionmentioning
confidence: 65%
“…Likewise, Ahmed et al [26] reported that increasing the dose of N fertilizer increased the ascorbic acid of Cactus Pears Fruits. Meanwhile, the application of cow manure and 100 kg ha 1 NPK fertilizer was able to reduce sweetness level of sweet corn, which is not in accordance with Taeotankencan et al [31], mentioning that the Artemisea lactiflora produced high vitamin C when treated with cow manure. The combination of chicken manure and NPK fertilizer at doses of 300-400 kg ha -1 was able to increase the pro-vitamin A content of sweet corn.…”
Section: Discussionmentioning
confidence: 65%
“…In the third harvest, however, the chlorophyll a+b content of the white mugwort manured with 10.08 t ha -1 of chicken fertilizer increased significantly compared with the control and the treatment of 187.50 kg ha -1 of chemical fertilizer ( Fig 1 ). This may be attributed to the effect of a higher chicken manure application increases the chlorophyll content, which positively affects photosynthesis and exhibits a higher of yield [ 15 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study showed that chicken manure application resulted in a highest yield and chlorophyll content in white mugwort when compared with the application of cow or bat manure. This suggests a potential for chicken manure in white mugwort cultivation [ 15 ]. Poultry manure was also reported to release nitrogen slowly, which resulted in significantly lower nitrate accumulation in plants [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rady et al reported that the organic matter of the compost could increase soil organic matter and provide more and better nutrients to the plant [24]. Taokaenchan et al found that chicken manure resulted in the highest yield and chlorophyll content in white mugwort compared with the application of cow or goat manure [25]. This highest chlorophyll will increase the effects of photosynthesis to increase the growth of green bean plants, especially in the number of flowers which will cause more and more fruits.…”
Section: After Ameliorant Applicationmentioning
confidence: 99%